A pH‐Driven Small‐Molecule Nanotransformer Hijacks Lysosomes and Overcomes Autophagy‐Induced Resistance in Cancer. Issue 35 (20th July 2022) - Ma, Zhao; Lin, Kai; Tang, Menghuan; Ramachandran, Mythili; Qiu, Reng; Li, Jin; Solano, Lucas N.; Huang, Yanyu; De Souza, Cristabelle; Abou‐Adas, Sara; Xiang, Bai; Zhang, Lanwei; et al.
Abstract: Smart conversion of supramolecular structures in vivo is an attractive strategy in cancer nanomedicine, which is usually achieved via specific peptide sequences. Here we developed a lysosomal targeting small‐molecule conjugate, PBC, which self‐assembles into nanoparticles at physiological pH and smartly converts to nanofibrils in lysosomes of tumor cells. Such a transformation mechanically leads to lysosomal dysfunction, autophagy inhibition, and unusual cytoplasmic vacuolation, thus granting PBC a unique anticancer activity as a monotherapy. Importantly, the photo‐activated PBC elicits significant phototoxicity to lysosomes and shows enormous advantages in overcoming autophagy‐caused treatment resistance frequently occurring in conventional phototherapy. This improved phototherapy achieves a complete cure of oral cancer xenografts upon limited administration. Our work provides a new paradigm for the construction of nonpeptide nanotransformers with biomedical activities. Abstract : The lysosomal targeting nonpeptide PBC (pheophorbide a–bisaminoquinoline conjugate) self‐assembles into nanoparticles at physiological pH and then transforms into nanofibrils upon the trigger of lysosomal pH. Due to such shape transformation, PBC not only inhibits tumor growth as a single agent but also mediates a convenient photodynamic therapy with promise to overcome the autophagy‐induced resistance and achieve tumor ablation.